COMPOSITION OF THE ESSENTIAL OIL OF TWO ENDEMIC CENTAUREA SPECIES FROM TURKEY - Kose, Y. B.; Altintas, A.; Tugay, O.; Uysal, T.; Demirci, B.; Ertugrul, K.; Baser, K. H. C. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Almost 600 species belonging to genus Centaurea L. are naturally distributed throughout Asia, North Africa and America (1). In the flora of Turkey, Centaurea is one of the richest genera. There the genus is represented by 189 species and 120 of them are endemic (2-3). Centaurea species have been widely used for their anti-dandruff, anti-diarrheic, anti-rheumatic, anti-inflammatory, choleretic, diuretic, digestive, stomachic, astringent, antipyretic, cytotoxic and antibacterial properties in folk medicine (4). Aerial parts of Centaurea sericeae Wagenitz and Centaurea ensiformis P.H. Davis were hydrodistilled for 3 hours using a Clevenger-type apparatus to produce a small amount of essential oil, which was trapped in n-hexane. Oils were analyzed by gas chromatography-mass spectrometry (GC-MS). Identification of the essential oil components was carried out by comparison of their relative retention times with those of authentic samples or by comparison of their relative retention index (RRI) to the series of n-alkanes. Computer matching against commercials (5-6), in-house “Baser Library of Essential Oil Constituents” built up by genuine compounds and components of known oils, as well as MS literature data (7-9), were used for the identification. Seventy-three and seventy-four compounds representing 84.7% and 91% of the essential oils were characterized from C. sericea and C. ensiformis, respectively. Caryophyllene oxide (10.6%), nonacosane (8.6%) and hexadecanoic acid (7%) were the main constituents in the oil of C. sericeae and ß-eudesmol (29.8%), hexadecanoic acid (8%) and caryophyllene oxide (7.6%) were the main constituents in the oil of C. ensiformis. References:1. Brummitt, R. K., 2004, Report of the Committee for Spermatophyta: 54, Taxon, 53 (3), 813-825. 2. Wagenitz G. 1975. Centaurea L. in: Flora of Turkey and the East Aegean Islands. 5, pp. 465-585, Edit. P.H. Davis, Edinburgh Univ. Press, Edinburgh, UK. 3. Uysal, T., 2008, Ann. Bot. Fen., 45, 137-140. 4. Arif R, Küpeli E., Ergun F. 2004., Gazi Üniversitesi Fen Bilimleri Dergisi, 17: 149-164. 5. McLafferty FW, Stauffer DB. 1989, The Wiley/NBS registry of mass spectral data, J Wiley and Sons: New York. 6.Joulain D. et al. 2001, Terpenoids and related constituents of essential oils. Library of MassFinder 2.1, Hamburg, Germany. 7. Joulain D., König W.A., 1998, The Atlas of spectra data of sesquiterpene hydrocarbons, EB-Verlag, Hamburg. 8.ESO 2000, 1999, The complete database of essential oils, Boelens Aroma Chemical Information Service, The Netherlands. 9.Jennings W.G., Shibamoto T., 1980, Quantitative analysis of flavour and fragrance volatiles by glass capillary GC, Academic Press, New York.